PEDAGOGICAL CONDITIONS FOR ORGANIZING INDEPENDENT ACTIVITIES OF MEDICAL STUDENTS IN THE PROCESS OF MUSIC THERAPY (International journal of artificial intelligence, 2024)
The article examines the pedagogical conditions for organizing independent activities of medical university students as part of their music therapy training. The importance of actively engaging students in independent work for developing their professional and personal qualities is emphasized. Research results are presented that confirm the effectiveness of using music therapy as a tool for enhancing students' emotional intelligence and stress resilience. Special attention is given to pedagogical conditions, including methodological support and ensuring an individualized approach.